Cooperação Sul-Sul entre Brasil e Angola no campo da defesa - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
This study analyses the South-South Cooperation practices between Brazil and Angola in the field of defense. Thus, it aims to understand how cooperation acts as a mechanism to ensure peace and the South Atlantic Ocean’s protection. For this, some of the firmed cooperation initiatives from Luís Inácio Lula da Silva’s presidency (2003-2010) to the first Dilma’s presidency (2011-2014) will be analyzed. For this, the study analyses the historical relation between Brazil and Angola; Brazil’s position in its South-South cooperation initiatives and the cooperation agreements in the field of Defense and Security involving these two countries, both in the bilateral and multilateral level (focusing in the Community of Portuguese Language Speaking Countries- CPLP- and the South Atlantic Peace and Cooperation Zone- ZPCSA-). Looking to conclude how effective the cooperation in this area is in the assertion of sovereignty and maintenance of peace in these South Atlantic countries and if the cooperation activities signed in multilateral bases have some influence in the bilateral cooperation agreements in the Defense field
Keywords: Cooperação internacional; Brasil (País); Angola (País); Defesa; Comunidade dos Países de Língua Portuguesa (CPLP); Zona de Paz e Cooperação do Atlântico Sul (ZOPACAS); CNPQ::CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL